2005
DOI: 10.1073/pnas.0506041102
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effects of Rho and mechanical stretch on stress fiber organization

Abstract: The small GTPase Rho regulates the formation of actin stress fibers in adherent cells through activation of its effector proteins Rhokinase and mDia. We found in bovine aortic endothelial cells that inhibitions of Rho, Rho-kinase, and mDia (with C3, Y27632, and F1F2⌬1, respectively) suppressed stress fiber formation, but fibers appeared after 10% cyclic uniaxial stretch (1-Hz frequency). In contrast to the predominately perpendicular alignment of stress fibers to the stretch direction in normal cells, the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
420
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(456 citation statements)
references
References 41 publications
34
420
2
Order By: Relevance
“…(ii) Cells "sense" the stiffness of their substrates and exert smaller tractions on more compliant substrates (Discher et al 2005). (iii) When substrates on which cells are cultured are subjected to cyclic strains, cells "avoid strain" such that stress-fibers form in the direction perpendicular to the imposed cyclic strain (Kaunas et al 2005). On the other hand, when cells cultured in three-dimensional (3D) tissues are subjected to cyclic strain, "strain alignment" is observed such that stress-fibers now form in the direction of the imposed cyclic strain (Nieponice et al 2007)…”
Section: Review Of the Key Biochemical Processes And Experimental Obsmentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) Cells "sense" the stiffness of their substrates and exert smaller tractions on more compliant substrates (Discher et al 2005). (iii) When substrates on which cells are cultured are subjected to cyclic strains, cells "avoid strain" such that stress-fibers form in the direction perpendicular to the imposed cyclic strain (Kaunas et al 2005). On the other hand, when cells cultured in three-dimensional (3D) tissues are subjected to cyclic strain, "strain alignment" is observed such that stress-fibers now form in the direction of the imposed cyclic strain (Nieponice et al 2007)…”
Section: Review Of the Key Biochemical Processes And Experimental Obsmentioning
confidence: 99%
“…In these experiments the cytoskeletal network formed perpendicular to the imposed cyclic strains and this was interpreted as strain avoidance (Buck 1980). Typically this avoidance increased with increasing imposed strain amplitude at a fixed frequency of loading (Kaunas et al 2005). This was interpreted as a sensitivity to imposed strain-rate (Wei et al 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, cells orient perpendicular to cyclic strain when cultured on stiff substrates or on biaxially constrained collagen gels (1)(2)(3)(4)(5)(6)(7). This phenomenon, called strain avoidance (SA), depends on the profile of the cyclic strain because the degree of cellular (re)orientation is proportional to the amplitude and frequency of the strain (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cellular alignment generally corresponds to the main SF direction (2), and experiments have shown that these acto-myosin bundles are essential for the reorientation of cells in response to cyclic strain (3,5). On the other hand, FAs are crucial to sense and interact with topographical stimuli, because they form the link between cells and their surroundings (34).…”
Section: Introductionmentioning
confidence: 99%